Performance of Bioactivators in Organic Waste Composting: Takakura and Composter Bag - Sri Sumiyati; Bimastyaji Surya Ramadan; Budi Prasetyo Samadikun; Anik Sarminingsih; Mochamad Arief Budihardjo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Population growth has significantly increased organic waste generation, requiring sustainable solutions like composting. This exploratory study evaluated the treatment-specific effectiveness of various bioactivators—EM4, biowash, ecoenzyme, and fermented stale rice solution—using Takakura and composting bag methods, with un-activated setups as controls. Composting was conducted for 42 days by monitoring physical and chemical parameters. Results showed that final physical characteristics and pH values (6.0–7.4) across all treatments complied with the Indonesian National Standard (SNI 19-7030-2004). Descriptive comparative analysis revealed that the combinations distinctly influenced final nutrient qualities. In the composting bag system, ecoenzyme performed best, achieving the most optimum and stable C/N ratio of 19.67 along with superior nitrogen retention (1.461%). Conversely, in the Takakura system, the fermented stale rice solution provided better organic matter stabilization compared to EM4 and control setups. Direct container-method comparison was valid only for the shared treatments (EM4 and Control), where the composting bag system exhibited better temperature and moisture stability, minimizing nutrient loss compared to the Takakura method. Ultimately, specific container-bioactivator pairings offer practical and sustainable alternatives for household and community-scale organic waste management.